Character Education In The Era Of Industrial Revolution 4.0 And Its Relevance To The High School Learning Transformation Process - HERIYANTO, HERIYANTO; SATORI, D.; KOMARIAH, A.; SURYANA, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study aims to discuss the approach to the implementation of character education management in the era of industrial revolution 4.0 (IR 4.0) and its impact on student learning transformation. The research method in the process of data collection is done through literature studies and interviews of character-building teachers and high school students. The results of this study showed that the teacher’s lack of understanding of IR 4.0 had an impact on the use of the character education approach used by teachers. RESUMEN Este estudio tiene como objetivo discutir el enfoque para la implementación de la gestión de la educación del carácter en la era de la revolución industrial 4.0 (IR 4.0) y su impacto en la transformación del aprendizaje de los estudiantes. El método de investigación en el proceso de recopilación de datos se realiza a través de estudios de literatura y entrevistas con maestros de formación de carácter y estudiantes de secundaria. Los resultados de este estudio mostraron que la falta de comprensión del maestro de IR 4.0 tuvo un impacto en el uso del enfoque de educación del carácter utilizado por los maestros.